Clinical course of pregnant women with SARS-CoV-2 infection with development of COVID-19: an integrative literature review (Research, Society and Development, 2021)
The SARS-CoV-2 pandemic causes health impacts that are still unknown and that are objectives of studies. Among these are how COVID-19 manifests itself in pregnant and postpartum women, what are the neonatal outcomes and what is the epidemiological profile of these women. To this end, an integrative literature review was conducted in the PubMed databases. The descriptors used to delimit the searches were pregnancy, SARS-CoV-2, COVID-19. Thus, 27 articles were selected at the end of the search. 92.6% of them were published in 2020, and the most prevalent country of origin was the United States, with 8 (29.62%) articles. Evidence shows that there is a relationship between a greater need for admission to the Intensive Care Unit and the use of ventilatory support among pregnant women with COVID-19. Pregnancy seems to be related to severe forms of the disease, but there are other influencing factors, such as obesity and diabetes mellitus. There was a higher proportion of black and Latina pregnant women among those affected, with an apparent increase in the risk of death among Latinas. Also, an increase in preterm births was noted when the severe form was present. Thus, it is evident that there is a relationship between the chance of worsening COVID-19 among pregnant women with SARS-CoV-2, especially those who are symptomatic and have comorbidities. In addition, increased rate of preterm births with the severe form. Thus, adopting preventive measures and vaccination among this population show as the main ways to avoid worsening, preterm births and deaths.